Surgical outcomes and complications associated with ovariectomy in the southern stingray Hypanus americanus - George, Robert H.; Buckner, Chris; Baine, Katherine; Steeil, James; White, Stacia; Handsel, Tim; Wyffels, Jennifer T. (Frontiers in Veterinary Science, 2024)
Southern stingrays (Hypanus americanus) are relatively large rays that are common and popular in public aquariums because of their size and gentle nature. In aquariums, as well as in the wild, female southern stingrays are fecund. They have a short gestation cycle and can sustain multiple pregnancies each year, each culminating with 2-10 young. This reproductive rate could quickly outpace capacity in managed care and result in a ray surplus. To prevent overpopulation, many aquaria have resorted to single sex groups with a preference for female-only populations. This is an effective way to control population growth, but forces the maintenance of two separated populations of rays; for females this interrupts normal reproductive cycling and replaces it with a protracted non-pregnant condition. An additional consideration is development of reproductive disease in females which is recognized by an enlarged, misshapen, and congested ovary with an abundance of cystic structures and an enlarged uterus with a thickened wall that is often filled with histotroph despite a non-pregnant status. There are no effective long-lasting medical treatments for this type of reproductive disease and mortality is often the result. This report describes a surgical technique for ovariectomy in southern stingrays including outcomes and complications. Ovariectomy as a surgical method prevents unwanted reproduction and has the benefit of reducing reproductive pathologies commonly observed in southern stingrays as they age. Seven stingrays 1-5.2 years old and 42-83.5 cm disc width underwent ovariectomy. After anesthesia, the ovary and a small amount of epigonal was excised via a left paralumbar incision. Four of the seven rays survived five or more years post-procedure. Two rays died acutely of coelomitis and one ray died of complications unrelated to the procedure. This report details a surgical procedure for ovariectomy in southern stingrays including outcomes, complications, and recommendations.